WRITING STRATEGIES USED BY ESL UPPER SECONDARY SCHOOL STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This study investigates the writing strategies employed by upper secondary school students learning English as a Second Language (ESL). Writing in a second language requires not only linguistic competence but also cognitive, metacognitive, and social strategies [1]. The research explores how learners plan, draft, revise, and monitor their writing, and how these strategies influence writing quality. Using a mixed-methods approach involving questionnaires, writing samples, and interviews, the study identifies the most frequently used strategies and their relationship to students’ proficiency levels [2]. The findings reveal that successful ESL writers use a wider range of cognitive and metacognitive strategies, while less proficient learners rely heavily on surface-level translation and memorization. The study highlights the importance of strategy-based instruction in improving ESL writing performance [3].